Assessment of a Biomass Cogeneration and Trigeneration Power Plant - Benamar, Damien (My University, 2009)
One of the biggest challenges of the 21st century is to reduce the greenhouse effect. In order to compete with fossil fuels that are emitting large amounts of greenhouse gases, emission-neutral solutions must be developed together with more efficient technological solutions. Biomass cogeneration is one of these new technologies that enables combined production of electricity and heat (cogeneration) while reducing the amount of fossil carbon dioxide emitted to the atmosphere. In France, cogeneration is not well developed, therefore the French Ministry of Environment and Sustainable Development has decided to launch calls for tenders focused on the production of green electricity from biomass fuel. This master´s thesis investigates the different technological options that exist to supply process heat to a French agro-food company while co-producing green electricity. Two different plants are studied. The first one currently requires 100 t/h of steam at a pressure of 14 bar. The new biomass plant will be designed for year-round production of 45 t/h of steam at two levels of pressure (30 t/h at 8 bar and 15 t/h at 14 bar). The second factory does not work with the same schedule and its steam demand is divided into two periods. The campaign period lasts 5000 h/year and requires 25 t/h of steam at a pressure of 12 bar while the inter-campaign period is evaluated to 3000 h/year with a steam demand of 5 t/h at the same pressure. The steam is currently produced with natural gas boilers. The results of the study indicate that installing a cogeneration system composed of an extraction-condensing steam turbine achieves a lower payback period (5 years) than a CHP plant with a back-pressure turbine (8 years). The use of a heat only boiler leads to a high payback period due to its lack of electricity production. From an energy performance point of view, using a back-pressure turbine leads to a total efficiency of around 80 %, whereas the extraction-condensing (EC) turbine total efficiency is equal to 60% on average. This efficiency decrease could guide the choice towards a back-pressure turbine. However, this technology is penalized by its low electricity production: 60% less electricity than for a EC turbine. Under current policy conditions in France, electricity production from renewable sources is favoured by a higher selling price on the grid (140 €/MWh compared to 64 €/MWh for purchased electricity). This means that the more electricity is produced the more the project will be profitable. This higher selling price is supported by several policies: the CSPE (economical contribution of the electricity consumers for the development of green electricity production), calls for tenders. In order to improve usage of the fuel energy supplied to the cogeneration power plant, it is possible to add an absorption chiller to the process. Cogeneration then becomes trigeneration and electricity, heat and also cooling are produced from the same source of energy. The addition of an absorption chiller does not have a big impact on the payback period (same payback period as for cogeneration) and enables a total efficiency increase from 62% to 67%. Even if this technology is not widespread nowadays, its use seems to be interesting for industries that need heat and cooling for their processes.
Keywords: Kemiteknik; Chemical Engineering